The Varieties and Revisions of Atheism - Schweiker, William (Zygon, 2005)
Abstract. The philosopher Antony Flew has argued for decades that theistic arguments cannot meet criteria of truth. In this essay I respond to Flew's recent announcement that research into the emergence of DNA provides grounds for rational belief in an intelligent orderer, a “God.” Flew's theistic turn is important for philosophers of religion and the wider science-and-religion dialogue. It becomes apparent, however, that Flew's “conversion” is not as decisive as one might imagine. While he admits growth in scientific and philosophical understanding, he rejects the idea of growth in religious understanding. Further, he endorses a version of “theoretical theism” while denying the practical importance of belief. Such denial of practical conviction is part of a modernist mindset that separates freedom from the embeddedness of human beings in the natural world. I conclude by noting that the entanglement of human action and wider physical processes, an entanglement seen emblematically in the environmental crisis, requires not only considering the importance of intelligence and order in the emergence of life but also the significance of human agency in claims about the divine and the natural world.